2022
DOI: 10.1002/mdc3.13488
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Measure of Visuospatial Impairment in Dementia with Lewy Bodies

Abstract: BackgroundBackground: Dementia with Lewy bodies (DLB) is a common cause of dementia with poor prognosis and high hospitalization rates. DLB is frequently misdiagnosed, with clinical features that overlap significantly with other diseases including Parkinson's disease (PD). Clinical instruments that discriminate and track the progression of cognitive impairment in DLB are needed. Objectives Objectives: The current study was designed to assess the utility of a mental rotation (MR) task for assessing visuospatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…We would propose that the currently proposed research criteria for MCI-LB should specify that the combination of clinically reported RBD (one core feature) that is confirmed by RSWA (one objective biomarker) in patients with MCI should be insufficient to meet a diagnosis of probable prodromal DLB. Previous studies have found utility of the SART, MR and BPP in detecting DLB core symptoms [ 43 , 44 , 46 ]; findings are less clear for patients in the prodromal stages of this disease. It is clear that more systematized work with larger cohorts and longitudinal assessment is required to confirm their future role.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…We would propose that the currently proposed research criteria for MCI-LB should specify that the combination of clinically reported RBD (one core feature) that is confirmed by RSWA (one objective biomarker) in patients with MCI should be insufficient to meet a diagnosis of probable prodromal DLB. Previous studies have found utility of the SART, MR and BPP in detecting DLB core symptoms [ 43 , 44 , 46 ]; findings are less clear for patients in the prodromal stages of this disease. It is clear that more systematized work with larger cohorts and longitudinal assessment is required to confirm their future role.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, it is possible that a larger sample size might be required to further evaluate this potential relationship. Previous findings have suggested that the MR task is reliant on visuospatial ability in DLB patients [ 44 ], which might suggest that visuospatial impairment occurs very early in DLB, before other core features emerge. An interesting additional observation was the number of patients that had low accuracy at the 0° condition from both groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations